Pengaruh Potongan Harga dan Kemudahan Penggunaan Terhadap Keputusan Penggunaan E-Wallet Shopee Pay - Risha Fatikha Sari (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
At this time technology is developing rapidly, this also triggers changes in human lifestyles as consumers. One of them is a cashless payment technique using an electronic wallet (e-wallet). The research entitled "The Influence of Discounts and Ease of Use on Decisions to Use E-Wallet Shopee Pay" aims to determine the effect of variables X1 and X2 on Y. By using a quantitative approach and multiple regression analysis techniques, the results show that the T test has a positive and partially significant effect. of the discount variable (X1) on the decision to use e-wallet shopee pay (Y) because T count > T table (4.640 > 1.984) with a significance value (0.000 < 0.05) then there is a positive and partially significant effect. between the ease of use variable (X2) on the decision to use e-wallet shopee pay (Y) because T count > T table (5,190 > 1,984) with a significance value (0.000 < 0.05). Furthermore, from the ANOVA test or F test, the results of F count > F table (54.386 > 3.09) with a significance level (0.000 < 0.05) can be concluded that X1 and X2 simultaneously affect Y.